IMPROVING OF THE ORGANIZATION OF INNOVATION MANAGEMENT OF THE BUILDING ENTERPRISE - A. G. Magomedov; T. A. Faruhov (Вестник Дагестанского государственного технического университета: Технические науки)
The article is devoted to improving the organization of innovative activity management of construction enterprises. Proposed a sequence of actions for improving the management of innovation, substantiated expediency of the use of such institutional innovation management as intrapreneurship and centers of subcontracting.